Factors associated with knowledge, attitudes, and practices of mixed crop-livestock farmers on Crimean Congo hemorrhagic fever (CCHF) and other zoonoses in Burkina Faso - Ilboudo, Abdoul K.; Dione, Michel M.; Nijhof, A.M.; Groschup, M.H.; Traoré, O.; Ilboudo, Guy S.; Tarnagda, Z.; Savadogo, M.; Bett, Bernard K. (Elsevier, 2025)
Background: The burden of zoonotic diseases remains high in low and middle-income countries. Among the prevalent zoonoses, Crimean-Congo hemorrhagic fever (CCHF) can pose economic and health threats, particularly among at-risk professionals. We aimed to assess the knowledge, attitudes, and practices regarding CCHF and other zoonoses among mixed-crop livestock farmers in the rural settings of Burkina Faso.